2018
DOI: 10.22159/ajpcr.2018.v11i7.26160
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge and Attitude Toward Depression and Schizophrenia: Findings From Quantitative Study in Uae

Abstract: Objective: The purpose of the current study to assess current attitude and knowledge of UAE population toward mental disorders, and to determine the stigma status of people with schizophrenia and depression.Methods: A represented sample of 430 participants was enrolled in the study. A descriptive qualitative survey was the study tool. The developed questionnaire was designed to be interview-administrated SPSS 24 used in data analysis. A correlation analysis was performed to test association. Oneway ANOVA and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…However, this study indicated that most participants reported good medication adherence and no/low level of stigma including having a positive attitude toward MDD. They believed that individuals with MDD were not crazy or dangerous, these findings were different from a relevant prior study in UAE [ 25 ]. A potential explanation for these discrepancies may be the use of different study instruments and the characteristics of the population, as most of our participants were female and had a high level of education.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…However, this study indicated that most participants reported good medication adherence and no/low level of stigma including having a positive attitude toward MDD. They believed that individuals with MDD were not crazy or dangerous, these findings were different from a relevant prior study in UAE [ 25 ]. A potential explanation for these discrepancies may be the use of different study instruments and the characteristics of the population, as most of our participants were female and had a high level of education.…”
Section: Discussioncontrasting
confidence: 77%
“…As per the literature review, 25.0–45.0% and 60.0% of the general population had poor knowledge of MDD and prejudice attitudes toward MDD, respectively [ 11 , 25 ]. In addition, 60.0–70.0% of individuals with MDD were reported to be medication non-adherent [ 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CPZ is metabolized by CYP3A4 (major) and CYP2D6 (minor) to produce two active metabolites didesmethyl cariprazine (DDCAR) and desmethyl cariprazine (DCAR). The overall pharmacological activity shown by this drug is due to the parent compound and its metabolite, which may also be a reason of its long half-life (2 to 4 d) [42]. The affinity towards receptors and medicinal effects are the basis of the classification of antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It comprises of components like identification of mental health disorders and knowledge of risk factors, causes, self-treatments, and professional help available. Currently, there is a widespread stigma about mental disorders, and they are sometimes believed to be untreatable, which causes delay or prevention from seeking help [6,7].…”
Section: Introductionmentioning
confidence: 99%